2011
DOI: 10.1073/pnas.1019312108
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-149*, a p53-responsive microRNA, functions as an oncogenic regulator in human melanoma

Abstract: The tumor suppressor p53 is activated in response to cellular stress to prevent malignant transformation by activation of the DNA repair machinery to preserve the cell, or by induction of apoptosis to eliminate the cell should the damage prove irrevocable. The gene encoding p53 frequently undergoes inactivating mutations in many human cancers, but WT p53 is often expressed at high levels in melanoma, which, as judged from the malignant nature of the disease, fails to act as an effective tumor suppressor. Here … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
142
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(144 citation statements)
references
References 43 publications
1
142
0
1
Order By: Relevance
“…miRNA is thereby a potential diagnostic and prognostic marker of TSCC with therapeutic potential (18)(19)(20). Previous studies revealed that miR-149 was downregulated in colorectal cancer, breast cancer, gastric cancer, glioma, melanoma and non-small cell lung cancer (21)(22)(23)(24)(25)(26). This study investigated the expression, biological functions and molecular mechanisms of miR-149 in TSCC.…”
Section: Discussionmentioning
confidence: 99%
“…miRNA is thereby a potential diagnostic and prognostic marker of TSCC with therapeutic potential (18)(19)(20). Previous studies revealed that miR-149 was downregulated in colorectal cancer, breast cancer, gastric cancer, glioma, melanoma and non-small cell lung cancer (21)(22)(23)(24)(25)(26). This study investigated the expression, biological functions and molecular mechanisms of miR-149 in TSCC.…”
Section: Discussionmentioning
confidence: 99%
“…6 These miRNAs have also been shown to play a role in controlling cell growth, apoptosis, senescence and autophagy in a p53-dependent fashion ( Table 1). [7][8][9][10][11][12][13][14][15][16][17][18][19][20] Recently, we identified miR-1246 as another novel p53 target miRNA. Interestingly, this miRNA regulates the expression of DYRK1A, a Down syndrome-associated kinase, 21 which inactivates a nuclear transcriptional factor called NFAT1C by phosphorylating it and preventing it from nuclear import.…”
Section: Mir-1246mentioning
confidence: 99%
“…This regulatory control is carried out through repression of gene expression at the post-transcriptional level (Bartel, 2009). Interestingly, miR-149 is found within the first intron of GPC1 (Jin et al, 2011) and its expression is downregulated in different solid tumors (Jin et al, 2011;Li et al, 2011;Øster et al, 2013;Wang et al, 2013). Moreover, overexpression of miR-149 in glioma and colorectal cancer cells results in reduced proliferation and migration, thus suggesting that miR-149 might play a role as a tumor suppressor (Jin et al, 2011;Li et al, 2011).…”
Section: Introductionmentioning
confidence: 99%